2011
DOI: 10.1007/s11145-011-9346-3
|View full text |Cite
|
Sign up to set email alerts
|

The simple view of second language reading throughout the primary grades

Abstract: In the Simple View of Reading proposed by Hoover and Gough (1990), reading comprehension is conceived as the product of word decoding and listening comprehension. It is claimed that listening comprehension or the linguistic processes involved in the comprehension of oral language strongly constrain the process of reading comprehension. In several studies, evidence for this theoretical framework has been provided for first language learners. In the present study, an attempt was made to find empirical evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
102
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(125 citation statements)
references
References 38 publications
17
102
2
4
Order By: Relevance
“…However, in subsequent years, as word‐level reading skills become established, language skills become stronger and more reliable predictors of reading comprehension (e.g., Catts, Fey, Zhang & Tomblin, ; Cutting & Scarborough, ; Francis et al, ; Storch & Whitehurst, ). This general observation is supported in L2‐based studies as well (Geva & Farnia, ; Verhoeven & van Leeuwe, ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, in subsequent years, as word‐level reading skills become established, language skills become stronger and more reliable predictors of reading comprehension (e.g., Catts, Fey, Zhang & Tomblin, ; Cutting & Scarborough, ; Francis et al, ; Storch & Whitehurst, ). This general observation is supported in L2‐based studies as well (Geva & Farnia, ; Verhoeven & van Leeuwe, ).…”
Section: Introductionsupporting
confidence: 77%
“…Support for the SVR model comes from studies of monolingual children (e.g., Cain, Oakhill & Bryant, ; Joshi & Aaron, ; Kendeou, Savage & van den Broek, ; Parrila, Kirby & McQuarrie, ). Although L2‐based studies converge in documenting that L2 reading comprehension is an area of weakness for L2 learners in comparison with their monolingual peers, they confirm that the SVR model is also supported with L2 learners (e.g., Carlisle, Beeman, Davis & Spharim, ; Geva & Farnia, ; Hutchinson, Whiteley, Smith & Connors, ; Nakamoto, Lindsey & Manis, ; Pasquarella, Gottardo & Grant, ; Verhoeven & van Leeuwe, ). Regardless of the research methodology used (cross‐sectional, auto‐regressive models or multiple measurement point growth analysis), the studies conducted to date point to the merit of an SVR model augmented with cognitive processes.…”
Section: Introductionmentioning
confidence: 93%
“…The contribution of word‐reading skills, oral reading fluency, and listening comprehension to reading comprehension performance has been well established (Berninger, Abbott, Vermeulen, & Fulton, ; Cadime et al., ; Catts, Adlof, & Weismer, ; Goff, Pratt, & Ong, ; Kim, ; Kim, Wagner, & Foster, ; Tilstra, McMaster, van den Broek, Kendeou, & Rapp, ), but the existence of bidirectional relations among those skills has been studied less frequently (Berninger & Abbott, ; Berninger et al., ; Jenkins, Fuchs, van den Broek, Espin, & Deno, ; Kim, ; Little et al., ; Verhoeven & van Leeuwe, , ). For research and intervention purposes, it is of the utmost importance to study the directionality of these relations and whether they change throughout elementary school grades.…”
mentioning
confidence: 99%
“…As international research has shown, L2 learners, while frequently not having problems in decoding, often have specific problems in reading comprehension (Melby-Lervåg and Lervåg 2013;Verhoeven and Leeuwe 2012). Researchers explain this specific comprehension deficit largely in terms of deficits in vocabulary knowledge (Hutchinson et al 2003;Verhoeven 2011).…”
Section: Introductionmentioning
confidence: 99%